2012
DOI: 10.1371/journal.pone.0047531
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infection among Children Presenting to a General Hospital Outpatient Clinic in Urban Nepal

Abstract: BackgroundThere are limited data on the etiology and characteristics of bloodstream infections in children presenting in hospital outpatient settings in South Asia. Previous studies in Nepal have highlighted the importance of murine typhus as a cause of febrile illness in adults and enteric fever as a leading bacterial cause of fever among children admitted to hospital.MethodsWe prospectively studied a total of 1084 febrile children aged between 2 months and 14 years presenting to a general hospital outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 45 publications
(66 reference statements)
6
27
0
Order By: Relevance
“…Pradhan et al also reported the similar rates of BSI in pediatric population in their study [26]. In this study, more pediatric patients (9.3%) were found with BSI as compared to adult patients (6.6%) and this difference was statistically significant ( p < 0.05).…”
Section: Discussionsupporting
confidence: 74%
“…Pradhan et al also reported the similar rates of BSI in pediatric population in their study [26]. In this study, more pediatric patients (9.3%) were found with BSI as compared to adult patients (6.6%) and this difference was statistically significant ( p < 0.05).…”
Section: Discussionsupporting
confidence: 74%
“…A study on fever of unknown origin in Ghana revealed that S. Typhi remains the most prevalent bacterial species causing bacterial blood stream infections (BBSI), where 40.7% (59/145) of BBSI were caused by S. Typhi (Groß et al, 2011). The same situation can be found in Kathmandu Valley where Salmonella infections are the leading cause of bloodstream infection among pediatric outpatients with fever (Pradhan et al, 2012). Clinical Studies in Minna (Nigeria) also revealed a high prevalence of typhoid fever (44.4%) among children within the age group 1-10 years which is also similar with an earlier report of 43.9% prevalence rate in Cebu City, India.…”
Section: Epidemiologysupporting
confidence: 84%
“…(A) Tempest regression of root-to-tip distance as (in the SNP alignment) a function of sampling time, with the root of the tree selected using heuristic residual mean squared (each point represents a tip of the maximum likelihood tree). The slope is a crude estimate of the substitution rate for the SNP alignment, the x-intercept corresponds to the e of the root node, and the R 2 is a measure of clocklike behaviour (B) Date randomisation test with the left most box plot showing the posterior substitution rate estimate from the SNP alignment of the data with the correct sampling times, and the remaining 20 boxplots showing the posterior distributions of the rate from replicate runs using randomised dates. The data are considered to have strong temporal structure if the estimate with the correct sampling times does not overlap with those from the randomisations.…”
Section: Supplementary Figurementioning
confidence: 99%
“…As in most developing countries, invasive bacterial infections account for a significant proportion of paediatric morbidity and mortality in Nepal 1,2 . Enteric fever, caused by Salmonella enterica serovars Typhi ( S. Typhi) and Paratyphi A ( S. Paratyphi A), is the most common cause of bloodstream infection in Nepal 1,2 and on a global scale causes an estimated 26 million cases of enteric fever annually of which a large proportion are in children 3,4 . In Nepal, it is estimated that 13% of febrile paediatric cases attending outpatient care are blood culture positive for S. Typhi or Paratyphi A 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation